Seven Rights of Medication Administration: Nurses' Knowledge, Attitude, and Compliance - Puspitasari, Shinta Dwi; Dewanto, Aryo; Holipah, Holipah; Muliawan, Arrasyid Indra (Fakultas Kedokteran Universitas Brawijaya, 2021)
Medication error becomes one of the main concerns in ensuring patient safety. In 2020, X Hospital reported medication error incidents. Although categorized near miss, the incidents should have been prevented. One of the methods to prevent medication errors is by applying the seven rights of medication administration. This study aimed to identify the inhibiting factors in the implementation of the seven rights of medication administration in X Hospital and obtain alternative solutions to those obstacles. This study used an analytic observational design with a cross-sectional design. Data were collected from observations and a survey. Observations and a survey through questionnaires to 20 nurses at X Hospital were made to see the implementation of the procedure. At the end of the data collection, interviews were conducted to find out the obstacles in the inpatient installation in applying the seven rights of medication administration. The results show that the main root causes of medication administration errors were the standard operating procedure (SOP) that has not been standardized and nurses' non-compliance behavior on the seven rights procedure. To resolve medication administration errors, the hospital manager should revise the SOP, conduct internal workshops, and perform scheduled supervision to the nurses.